2021
DOI: 10.1080/07347332.2021.1887430
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors’ perceived vulnerability to COVID-19 and impacts on cognitive, affective, and behavioral responses to the pandemic

Abstract: Study objectives: Given the uncertainty COVID-19 has caused for individuals with prior medical conditions, we examined the extent to which cancer survivors consider themselves at risk for the global COVID-19 pandemic (henceforth COVID), both in general and due to their cancer history. Additionally, we evaluated whether perceived vulnerability to COVID among cancer survivors predicts their cognitive/affective and behavioral responses to the pandemic. Design/sample: Cancer survivors who completed primary cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Participants who had cancer said they used all of their all resources to cope with negative cognitions, which are repetitive and intrusive. Similarly, given the hardship of the cancer process, recent studies showed that Covid-19 predicts catastrophic cognitions among cancer survivors (Poort et al, 2021;Slivjak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who had cancer said they used all of their all resources to cope with negative cognitions, which are repetitive and intrusive. Similarly, given the hardship of the cancer process, recent studies showed that Covid-19 predicts catastrophic cognitions among cancer survivors (Poort et al, 2021;Slivjak et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Participants who had cancer said they used all of their all resources to cope with negative cognitions, which are repetitive and intrusive. Similarly, given the hardship of the cancer process, recent studies showed that Covid‐19 predicts catastrophic cognitions among cancer survivors (Poort et al, 2021; Slivjak et al, 2021). Cancer survivors are catastrophizing related to Covid‐19 (Öcalan & Üzar‐Özçetin, 2021); the current findings suggest that cancer survivors who observe themselves as more vulnerable to Covid‐19 may engage in greater catastrophic thinking connected to losing someone they love.…”
Section: Discussionmentioning
confidence: 99%
“…Fear, concern, and prevention behaviors associated with the COVID‐19 pandemic were measured using the Coronavirus Fear Inventory (CFI; baseline α = 0.83), 16 a 7‐item measure adapted from the Ebola Fear Inventory, 26 as well as a cancer survivor‐specific version of the CFI, consisting of three items from the CFI that assessed COVID‐19 fears specific to cancer survivorship status (baseline α = 0.95; e.g., ‘As a cancer survivor, to what extent do you believe you have a higher chance of dying from COVID‐19? (compared to others your age)’) 16 . We included these measures to differentiate the effects of mental health symptoms from fears/concerns about the pandemic specifically.…”
Section: Methodsmentioning
confidence: 99%
“…The surveys used validated, wisely-used measures to assess anxiety and depression symptoms-the Generalized Anxiety Disorder-7 scale (compared to others your age)'). 16 We included these measures to differentiate the effects of mental health symptoms from fears/ concerns about the pandemic specifically. were conducted in R using the 'stats' package.…”
Section: Anxiety and Depression Symptomsmentioning
confidence: 99%
See 1 more Smart Citation